FAIL-STOP DESIGNATED RECIPIENT SIGNATURE SCHEME BASED ON ELLIPTIC CURVE DISCRETE LOGARITHM PROBLEM - Tahat, Nedal (Italian Journal of Pure and Applied Mathematics, 2013)
This paper describes a new digital signature called fail-stop designated recipient signature scheme based on elliptic curve discrete logarithm (ECDLP). The scheme allows a signer and an intended recipient to co-operatively provide a proof of forgery if an attacker can successfully forge a signature on a message m. The scheme also provides that the intended recipient is the only entity to verify the resulting signature and capable to prove the validity of signature to any third party. With this property, we show that our new signature scheme is the best alternative to solve certain problems concerning the protection of confidential documents especially those which are personally sensitive (to the owner) and is also applicable for group of recipients to verify a signature jointly (shared verification) in a group oriented environment. The scheme utilizes the inherent advantage of elliptic curve cryptosystem in terms of smaller key size and lower computational overhead to its counterpart public cryptosystems such as RSA and AlGamal. Compared with the Ismail and Yahya scheme [1], we show that our scheme is more eﬃcient in terms of both computation and communication complexity.